The Third Revolution in Sequencing Technology. Issue 9 (September 2018) - van Dijk, Erwin L.; Jaszczyszyn, Yan; Naquin, Delphine; Thermes, Claude
Abstract : Forty years ago the advent of Sanger sequencing was revolutionary as it allowed complete genome sequences to be deciphered for the first time. A second revolution came when next-generation sequencing (NGS) technologies appeared, which made genome sequencing much cheaper and faster. However, NGS methods have several drawbacks and pitfalls, most notably their short reads. Recently, third-generation/long-read methods appeared, which can produce genome assemblies of unprecedented quality. Moreover, these technologies can directly detect epigenetic modifications on native DNA and allow whole-transcript sequencing without the need for assembly. This marks the third revolution in sequencing technology. Here we review and compare the various long-read methods. We discuss their applications and their respective strengths and weaknesses and provide future perspectives. Highlights: Long-read/third-generation sequencing technologies are causing a new revolution in genomics as they provide a way to study genomes, transcriptomes, and metagenomes at an unprecedented resolution. SMRT and nanopore sequencing allow for the first time the direct study of different types of DNA base modifications. Moreover, nanopore technology can sequence directly RNA and identify RNA base modifications. Owing to the portability of the MinION and the existence of extremely simple library preparation methods, nanopore technology allows the performance of high-throughput sequencing for the first time in the field and at remote places. This is of tremendous importance for the survey of outbreaks in developing countries.